Single-Lumen and Multi-Lumen Poly(Ethylene Glycol) Nerve Conduits Fabricated by Stereolithography for Peripheral Nerve Regeneration In Vivo - Evangelista, Maristella S.; Perez, Mireya; Salibian, Ara A.; Hassan, Jeffrey M.; Darcy, Sean; Paydar, Keyianoosh Z.; Wicker, Ryan B.; Arcaute, Karina; Mann, Brenda K.; Evans, Gregory R. D. (Journal of Reconstructive Microsurgery, 2015)
Background The use of nerve conduits to facilitate nerve regrowth after peripheral nerve injury is limited to defects less than 3 cm. The purpose of this study is to determine the capability of novel single and multi-lumen poly(ethylene glycol) (PEG) conduits manufactured by stereolithography to promote peripheral nerve regeneration.Materials and Methods Eight Sprague Dawley rats with sharp transection injuries of the sciatic nerve were randomly assigned to receive single-lumen or multi-lumen PEG conduits to bridge a 10-mm gap. Sciatic nerve and conduit samples were harvested after 5 weeks, and axon number, myelin thickness, fiber diameter, and g-ratio were analyzed. The contralateral intact nerve was also harvested for comparison.Results Partial nerve regeneration was observed in three out of four single-lumen conduits and one out of four multi-lumen conduits. Axon number in the single-lumen regenerated nerve approached that of the contralateral intact nerve at 4,492 ± 2,810.0 and 6,080 ± 627.9 fibers/mm2, respectively. The percentage of small fibers was greater in the single-lumen conduit compared with the intact nerve, whereas myelin thickness and g-ratio were consistently greater in the autologous nerve. Axon regrowth through the multi-lumen conduits was severely limited.Conclusion Single-lumen stereolithography-manufactured PEG nerve conduits promote nerve regeneration, with regenerating axon numbers approaching that of normal nerve. Multi-lumen conduits demonstrated significantly less nerve regeneration, possibly due to physical properties of the conduit inhibiting growth. Further studies are necessary to compare the efficacy of the two conduits for functional recovery and to elucidate the reasons underlying their differences in nerve regeneration potential.
Keywords: peripheral nerve repair; stereolithography; nerve conduit; poly(ethylene glycol); multi-lumen; single-lumen